A Dual Role of DDX3X in dsRNA-Derived Innate Immune Signaling - Kwon, Juntae; Choi, Hyeongjwa; Han, Cecil (Frontiers in Molecular Biosciences, 2022)
DEAD-Box Helicase 3 X-Linked (DDX3X) is essential for RNA metabolism and participates in various cellular processes involving RNA. DDX3X has been implicated in cancer growth and metastasis. DDX3X is involved in antiviral responses for viral RNAs and contributes to pro- or anti-microbial responses. DDX3X also plays a role in immune cell production, differentiation, composition, and proliferation. Accumulating research suggests a more complex role of DDX3X in regulating double-stranded RNAs (dsRNAs) and human disease. A better understanding of DDX3X on dsRNAs will provide foundational knowledge for understanding innate immune sensing, anti-microbial immunity, inflammation, immune cell homeostasis, and developing novel therapeutics for infectious, immune-mediated diseases, and cancer. Here, we discuss the role of DDX3X in viral dsRNA- or endogenous dsRNA-mediated immune signaling pathways.